Contribution to the Study of trichobezoar. Apropos of a giant case - Gálvez Muñoz, Segundo A. (1965)
The trichobezoar is mainly an accumulation of hair and, by extension , sheep wool threads in the stomach or intestines of humans and animals. If you are human , usually nervous and insane persons or in certain occupations, such as sheep are shorn res , they acquire the habit of swallowing hair, almost inadvertently ( Teschendorí , 16-6 ) . It is a condition that belongs to the chapter on foreign bodies located in the abdomen, especially in the stomach , is actually a benign tumor that is formed by the accumulation of hair caused by successive intake over months and years , which cumulatively form a mesh so tightly intertwined that it is impossible to recover a full hair is: trichobezoar . This paper is therefore intended to analyze and contribute to the study of Trichobezoar about a case recently observed . As it is a fairly rare disease entity , which among us is not described yet , I have taken as my dissertation topic of Bachelor.